Toward ‘post-REDD+ landscapes’: Mexico’s community forest enterprises provide a proven pathway to reduce emissions from deforestation and forest degradation - Bray, D.B. (Center for International Forestry Research, 2010)
Regions where community forest enterprises dominate the landscape have low to non-existent deforestation, sustainable forest management, enhancement of carbon stocks, forest conservation and substantial generation of sustainable livelihoods. Corruption and deforestation are also associated with some Mexican forest communities, but these regions have created a sector with hundreds of well-managed community forests that contribute to the mitigation of, and adaptation to, climate change. Some 60–70% of Mexican forests are now owned by communities. Forests and land redistribution to local communities that began with the Mexican Revolution (1910–1917) continued until 1992, with a major surge from 1958 to 1976. The agrarian and forest tenure reforms in Mexico served as a foundation for village-level democratic decision-making around forest management. This model clearly defines rights holders and the agricultural and forest territory that they own. Mexico experienced a period of industrial logging concessions on community lands, but both government and communities sought reform in the 1970s, so that timber rights and greater authority over forest management devolved to communities. Mexican forest laws in recent decades have frequently provided a supportive policy environment for community forestry. An estimated 2300 communities regularly log under management plans in Mexico . Mexican community forest enterprises with forest common properties operate at all levels of this vertically integrated industrial sector.